Modic Changes Are Not Associated With Long-term Pain and Disability: A Cohort Study With 13-year Follow-up. Issue 17 (1st September 2019) - Udby, Peter Muhareb; Bendix, Tom; Ohrt-Nissen, Søren; Lassen, Michael Ruud; Sørensen, Joan Solgaard; Brorson, Stig; Carreon, Leah Y.; Andersen, Mikkel Østerheden
Abstract : Study Design: A comparative cohort study with 13-year follow-up. Objective: To assess whether Modic changes (MCs) are associated with long-term physical disability, back pain, and sick leave. Summary of Background Data: Previous studies have shown a conflicting association of low back pain (LBP) with MCs and disc degeneration. The long-term prognosis of patients with MCs is unclear. Methods: In 2004 to 2005, patients aged 18 to 60 with daily LBP were enrolled in an randomized controlled trial study and lumbar magnetic resonance imaging (MRI) was performed. Patients completed numeric rating scales (0–10) for LBP and leg pain, Roland-Morris Disability Questionnaire (RMDQ), LBP Rating Scale for activity limitations (RS, 0–30), inflammatory pain pattern and sick leave days due to LBP at baseline and 13 years after the MRI. Patients were stratified based on the presence (+MC) or absence (−MC) of MCs on the MRI. Results: Of 204 cases with baseline MRI, 170 (83%) were available for follow-up; 67 (39%) with MCs and 103 (61%) without MCs. Demographics, smoking status, BMI, use of antibiotics, LBP, leg pain, and inflammatory pain pattern scores at baseline and at 13-year follow-up were similar between the two groups. Also, baseline RMDQ was similar between the +MC and −MC groups. At 13 years, the RMDQ score was statistically significant better in the +MC group (7.4) compared with the −MC group (9.6, P  = 0.024). Sick leave days due to LBP were similar at baseline but less in the +MC group (9.0) compared with the −MC group (22.9 d, P  = 0.003) at 13 years. Conclusion: MCs were not found to be negatively associated with long-term pain, disability, or sick leave. Rather, the study found that LBP patients with MCs had significantly less disability and sick-leave at long-term follow-up. We encourage further studies to elucidate these findings. Level of Evidence: 2 Abstract : A cohort study of LBP patients with Modic changes. Eighty-three percent of cases (n = 204) are available at 13-year follow-up. MCs were not found to be negatively associated with long-term pain, disability, or sick leave. Rather, the study found that LBP patients with MCs had significantly less disability and sick-leave at long-term follow-up.